Fieldwork Educators' Perspectives: Professional Behavior Attributes of Level II Fieldwork Students - Marcie K. Campbell; Katelyn Corpus; Tracy M. Wussow; Teresa Plummer; Debra Gibbs; Shelley Hix (Scholarworks @ WMU, 2015)
A review of the literature revealed a lack of consistent expectations for professional behaviors required of level II fieldwork students. This study sought to obtain a consensus of perspectives of level II fieldwork educators by asking, "What are the essential professional behavior attributes for level II fieldwork students?" Delphi methodology was used to collect data in two rounds of surveys. In the first, 49 fieldwork educators listed professional behavior attributes they believed to be important for fieldwork students. The data was synthesized into themes for distribution in the second survey, which were identified as essential, non-essential, or site-specific by 53 participants. The 218 different professional behavior attributes provided by Survey 1 respondents were categorized into 22 attribute themes. In Survey 2, 20 of the 22 attribute themes reached a consensus level of at least 75% and five reached 100% agreement. These results show a current perspective of what fieldwork educators value in level II fieldwork students and may be informative to occupational therapy faculty, students, and fieldwork educators.